Diagnóstico del clima laboral de los servidores públicos del Gobierno Autónomo Descentralizado Municipal del Cantón Catamayo Año 2022. - Torres Castillo, Johanna Alexandra (2023)
he following research work is designed to diagnose the work environment at the GAD (Autonomous Decentralized Municipal Government Municipal) of the Catamayo canton during the year 2022, with the following objectives: an assessment of the work environment at the GAD, identification of the factors influencing public servants, and a proposal for improving the work environment, using the factors influencing the work environment as a reference. To collect the information, a previously prepared survey was used, which contains the eight factors of the work environment (autonomy, cohesion, trust, pressure, support, recognition, equity and innovation), formed using the Likert scale. However, it was applied to a population of 153 servers, which 143 respondents are subordinates, likewise, 9 respondents are departmental heads, likewise, and an interview was conducted with the Mayor as the highest authority of the Canton, thus finding the main deficiencies that allowed to make a proposal to improve the work environment. The present investigation concluded under the fulfillment of the three specific objectives, which in turn, fulfilled the established general objective; allowing as a result the proposal to improve the work environment taking as a reference the factors that influence, among the eight dimensions diagnosed in the institution, the pressure and equity factor require the establishment of strategies that contribute to the improvement of the work environment of the public servants of the institution